2018
DOI: 10.1007/s10763-018-9892-0
|View full text |Cite
|
Sign up to set email alerts
|

Task Design Principles for Heuristic Refutation in Dynamic Geometry Environments

Abstract: Task design is increasingly recognised as crucial for enhancing student learning of mathematics. Even so, and despite the significance of mathematical activity related to proofs and counterexamples in school mathematics, the task design principles underpinning students' success in proof-related activity remains under-explored in mathematics education research. What is more, although the affordances of using dynamic geometry environments (DGEs) have been established in the literature, task design in DGEs remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…Existing studies have tended to emphasise the relative affordances of DGEs in comparison with those of paper-and-pencil environments. The dragging function of DGEs, leading to a variety of diagrams, enables students to engage in dynamic mathematical activity where they can produce conjectures by themselves, discover counterexamples and come up with ideas regarding how to prove conjectures (Baccaglini-Frank and Mariotti 2010; Baccaglini-Frank et al 2018; Komatsu and Jones 2019). This is partly the case with the lessons described in this article, as the students discovered the existence of different cases through dragging and investigated a conjecture generalising the original statement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have tended to emphasise the relative affordances of DGEs in comparison with those of paper-and-pencil environments. The dragging function of DGEs, leading to a variety of diagrams, enables students to engage in dynamic mathematical activity where they can produce conjectures by themselves, discover counterexamples and come up with ideas regarding how to prove conjectures (Baccaglini-Frank and Mariotti 2010; Baccaglini-Frank et al 2018; Komatsu and Jones 2019). This is partly the case with the lessons described in this article, as the students discovered the existence of different cases through dragging and investigated a conjecture generalising the original statement.…”
Section: Discussionmentioning
confidence: 99%
“…It is within this type of generalisation that DGEs can play a key role, because the dragging function of DGEs allows for relatively easy access to multiple diagrams, while keeping certain the geometrical relationships imposed on the diagrams. The successive transformation of diagrams can highlight continuity and discontinuity between different configurations within an identical statement (Komatsu and Jones 2019).…”
Section: Proving and Generalisation In Geometrymentioning
confidence: 99%
“…Researchers have argued that dynamic technologies have to be a tool used to develop mathematical thinking rather than simply a tool that executes mathematical operations (Richard et al, 2019). By using dynamic technologies as ways to build knowledge inductively, students can be supported to focus on the more general aspects of the cases they examine and move to thinking more deductively (Baccaglini-Frank, 2019; Komatsu & Jones, 2019;Lachmy & Koichu, 2014).…”
Section: Mathematical Reasoning With Dynamic Technologymentioning
confidence: 99%
“…The uses of example for demonstrating, confirming, or refuting existential statements are often found to be non-trivial. Komatsu and Jones (2018) reported that students often encounter difficulties in formulating counter-example diagrams. They found that DGEs were highly useful in overcoming these difficulties and helping students produce counter-example diagrams.…”
Section: Connecting Examples and Universal Statements: The Interaction Between Proving And Exemplifyingmentioning
confidence: 99%